Pengaruh Curah Hujan pada Produksi Padi Gogo di Indonesia - Agung Budi Santoso; Tavi Supriana; Moral Abadi Girsang (Jurnal Ilmu Pertanian Indonesia, 2022)
Upland rice has high potential development that causes the potential of dry land in Indonesia is quite large. However, the productivity of upland rice and its contribution to national paddy production is still low. Upland rice mostly is cultivated based on rainfall so productivity of upland rice depends on fluctuation of rainfall at the area. Theoretically, Indonesia has three different rainfall types, namely; equatorial, monsoonal, and local. This study aimed to identify the effect of rainfall on upland rice production. This study used secondary data consisted of upland rice yield, precipitation, and harvested area in 1990–2017. Data were analyzed by quadratic nonlinear regression and then It was analyzed by Mann-Whitney different test. Selected location were North Sumatera Province, West Kalimantan, Central Sulawesi, East Java, South Sulawesi, South Kalimantan, and Maluku. Results show that three rainfall area types statistically differences. Precipitation at Equatorial area influences upland rice yield by 3.15 tons. Furthermore, precipitation at monsoon and local area have effects on reducing production by -0.17 ton and -10.66 ton respectively. Keywords: nonlinear regression, precipitation, productivity, upland rice